2023
DOI: 10.21608/ijma.2023.220098.1723
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serum Myeloperoxidase in Prediction of Severe Bronchial Asthma

Abstract: Article informationBackground: Bronchial asthma increasing all over the world and the need of a gold-standard biomarkers for prediction of asthma and follow up of treatment is mandatory. However, it is still not existing. Aim of the work:To measure the serum level of plasma myeloperoxidase [MPO], and its correlation with respiratory function as well as its predictive power of asthma and its severity. Patients and Methods:The study recruited 130 patients with asthma, with age and sex-matched other 130 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The greater MPO levels did not, however, substantially correspond with the asthma control levels. Another, adult study by Hassan et al (16) showed that MPO levels were significantly greater in the bronchial asthma patients than controls. The same results were reported by Aldhalmi et al (17) Regarding the validity of MPO in discriminating patients with pneumonia, ROC curve analysis showed that serum level of MPO > 41.8 can be used as a marker with sensitivity of 65.5% and specificity of 67.4% in diagnosing patients with pneumonia.…”
Section: Discussionmentioning
confidence: 95%
“…The greater MPO levels did not, however, substantially correspond with the asthma control levels. Another, adult study by Hassan et al (16) showed that MPO levels were significantly greater in the bronchial asthma patients than controls. The same results were reported by Aldhalmi et al (17) Regarding the validity of MPO in discriminating patients with pneumonia, ROC curve analysis showed that serum level of MPO > 41.8 can be used as a marker with sensitivity of 65.5% and specificity of 67.4% in diagnosing patients with pneumonia.…”
Section: Discussionmentioning
confidence: 95%